THE EFFECTIVENESS OF USING WARM COMPRESSES AND BIRTHING BALLS ON THE ANXIETY LEVEL OF THE ACTIVE PHASE OF THE FIRST STAGE OF LABOR - Adriana Palimbo; Fadhiyah Noor Anisa; Lisda Handayani; Uswatun Hasanah (HEALTH SCIENCES International Journal, 2023)
Background: Labor accompanied by pain reaches 90% of events; however, in developed countries, around 7-14% give birth without pain. Several attempts were made through non-pharmacological methods, including warm compresses and a birthing ball, to reduce anxiety into the active phase of the first stage of labor. Objective: This study aims to analyse the effectiveness of warm compresses and birthing balls on the anxiety scale of women in labor during the active phase I. Methods: This quasi-experimental study involved 30 primiparous women and multiparas with a gestational age of 36-40 weeks in the third trimester. Maternity mothers were divided into two groups. The first group obtained warm compresses, while the second group received warm compresses and birthing balls. The Hamilton Anxiety Rating Scale (HARS) was used before and after the intervention to measure labor pain. Results: The independent t-test showed that warm compresses combined with the birthing ball were more effective in reducing anxiety levels than just warm compresses (p-value 0.030<0.05). The average score of respondents' anxiety after being given a warm compress was 48.60, and the average score of respondents' anxiety after being given a warm compress and birthing ball was 42.87. Conclusion: The non-pharmacological method of using warm compresses with the birthing ball considerably reduces women's anxiety level in labor in the first active phase compared to only the single method of wUsarm compresses.